FACTORS AFFECTING THE OCCURRENCE CARIES DENTAL ON ELEMENTARY SCHOOL STUDENTS IN SD N PADANGSARI II BANYUMANIK SEMARANG - Nugraheni, Hermien; Wiyatini, Tri; Afia, Maria Okta (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Caries is the problems that were encountered in the field of dental health. Dental caries is an important issue for school student because it not only causes complaints of pain, but also spread the infection to other parts of the body resulting in declining productivity. This study aims to determine what factors are likely to influence the case of caries in elementary school student Padangsari II District Banyumanik 2016. Methods: This type of research used descriptive analysis with Cross sectional. Samples in this study were 50 students in grade 5 SDN Padasari II who have dental caries remains were taken with purposive sampling method. Collecting data in this study using clinical examination and the distribution of questionnaires. The questionnaire used in this study had previously been through validity and reliability test conducted on 35 students of SDN Meteseh District Tembalang. Methods of analysis used data using statistical calculations using Linear Logistic Regression Test. Results: The results in the region Padangsari II showed that the Plaque Index value exp (B) = 5,667, behavioral factors (knowledge exp (B) = 3.000, Attitude exp (B) = 3.000, factors action exp (B) = 2,333, salivary hydration exp (B) = 1,520, salivary viscosity exp (B) = 1,500, salivary pH exp (B) = 1.222. OHIS exp (B) = 1.143, the factor of health care exp (B) = 0,667, heredity exp (B) = 0.667, environmental factors exp ( B) = 0.429. Conclusion: In this study it can be concluded that the plaque index is the biggestt factor in influencing the cavity on the case if community health centers in the region Padangsari II.Because it has the highest score is exp (B) = 5,667.Â